Assessment and Synthesis of 50 Years of Published Drainage Phosphorus Losses. Issue 5 (1st September 2016) - Christianson, L. E.; Harmel, R. D.; Smith, D.; Williams, M. R.; King, K.
Abstract : The prevalence of anthropogenic drainage systems in intensively cropped areas across North America combined with the degradation of important freshwater resources in these regions has created a critical intersection where understanding phosphorus (P) transport in drainage waters is vital. In this study, drainage‐associated nutrient load data were retrieved and quantitatively analyzed to develop a more comprehensive understanding of the P loading and crop yield impacts of agronomic management practices within drained landscapes. Using the Drain Load table in the MANAGE (Measured Annual Nutrient loads from AGricultural Environments) database, the effect of factors such as soil characteristics, tillage, and nutrient management on P loading were analyzed. Across site‐years, generally less than 2% of applied P was lost in drainage water, which corroborates the order of magnitude difference between agronomic P application rates and P loadings that can cause deleterious water quality impacts. The practice of no‐till significantly increased drainage dissolved P loads compared with conventional tillage (0.12 vs. 0.04 kg P ha −1 ). The timing and method of P application are both known to be important for P losses, but these conclusions could not be verified due to low site‐year counts. Findings indicate there is a substantial need for additional field‐scale studies documenting not only P losses in drainage water but also important cropping management, nutrient application, soil property, and drainage design impacts on such losses. Core Ideas: Used the MANAGE water quality database to evaluate factors affecting drainage P loss. Generally less than 2% of applied P was lost in drainage across all studies. P application timing/method are important, but sparse data limited the assessment. The scarcity of drainage P data relative to N is a critical gap in understanding.